Gender and collective action: motivations, effectiveness and impact - Pandolfelli, Lauren; Meinzen-Dick, Ruth S.; Dohrn, Stephan (Wiley, 2008)
Gender is often a key determinant of people's abilities to participate in collective action, yet there has been relatively little research on the links between gender and collective action. This article, and the ones that follow in this special issue, explore the intersection of these two fields. We present three entry points for a gendered analysis of collective action: motivations to engage in collective action; effectiveness of collective action (as defined by group objectives and the process by which the group works to meet those objectives); and impact of collective action on gender equity. We discuss each of these themes by highlighting key issues presented in the articles in this special issue.